Pengaruh Reward Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Optima Mandiri Persada - Mayangsari, Andini; Budi Santoso, Arief (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Abstrak. To determine the partial effect of rewards on employee performance. To determine the partial effect of work discipline on employee performance. To determine the simultaneous effect of rewards and work discipline on employee performance at PT. Optima Mandiri Persada. The type of research used in this study is quantitative research. The population is 63 employees of PT. Optima Mandiri Persada. Using total sampling or saturation, that is, the entire population is sampled. The analysis results show that reward (X1) has a positive and significant influence on employee performance (Y), with the regression equation Y = 15.302 + 0.846 X1. The coefficient of determination is 56%. The hypothesis test results indicate that the t-value exceeds the t-table (2.373 > 2.0030), suggesting statistical significance then Ha is accepted and H0 is rejected . Similarly, work discipline (X2) also has a positive and significant impact on employee performance (Y), with the regression equation Y = 6.707 + 1.065 X2. The coefficient of determination is 76.5%, and the t-value is greater than the t-table (7.919 > 2.0030), indicating significance. Simultaneously, reward (X1) and work discipline (X2) significantly and positively affect employee performance (Y), as represented by the regression equation Y = 5.750 + 0.242 X1 + 0.870 X2. The coefficient of determination is 78.5%, while the remaining 21.5% is explained by other variables outside the model then Ha is accepted and H0 is rejected . The F-test shows that the F-value exceeds the F-table (109.548 > 3.15), So it can be said that Rewards (X1) and Work Discipline (X2) together have an influence on Employee Performance (Y). Keywords: Reward, Work Discipline and Employee Performance.